Unveiling pelagic-benthic coupling associated with the biological carbon pump in the Fram Strait (Arctic Ocean) - Simon Ramondenc; Damien Eveillard; Katja Metfies; Morten H. Iversen; Eva-Maria Nöthig; Dieter Piepenburg; Christiane Hasemann; Thomas Soltwedel (Nature Communications)
Abstract Settling aggregates transport organic matter from the ocean surface to the deep sea and seafloor. Though plankton communities impact carbon export, how specific organisms and their interactions affect export efficiency is unknown. Looking at 15 years of eDNA sequences (18S-V4) from settling and sedimented organic matter in the Fram Strait, here we observe that most phylogenetic groups were transferred from pelagic to benthic ecosystems. Chaetoceros socialis, sea-ice diatoms, Radiolaria, and Chaetognatha are critical components of vertical carbon flux to 200 m depth. In contrast, the diatom C. socialis alone is essential for the amount of organic carbon reaching the seafloor. Spatiotemporal changes in community composition show decreasing diatom abundance during warm anomalies, which would reduce the efficiency of a diatom-driven biological carbon pump. Interestingly, several parasites are also tightly associated with carbon flux and show a strong vertical connectivity, suggesting a potential role in sedimentation processes involving their hosts, especially through interactions with resting spores, which could have implications for pelagic-benthic coupling and overall ecosystem functioning.